The Pharmacological or Genetic Blockade of Endogenous De Novo Fatty Acid Synthesis Does Not Increase the Uptake of Exogenous Lipids in Ovarian Cancer Cells - Grunt, Thomas W.; Lemberger, Lisa; Colomer, Ramón; López−Rodríguez, María Luz; Wagner, Renate (Frontiers in Oncology, 2021)
Ovarian cancer(OC) is a serious threat to women worldwide. Peritoneal dissemination, ascites and omental metastasis are typical features for disease progression, which occurs in a micro-environment that is rich in high-energy lipids. OC cells require high amounts of lipids for survival and growth. Not only do they import lipids from the host, they also produce lipids de novo. Inhibitors of fatty acid(FA) synthase(FASN) – the rate-limiting enzyme of endogenous FA synthesis that is overexpressed in OC – induce growth-arrest and apoptosis, rendering them promising candidates for cancer drug development. However, cancer researchers have long hypothesized that the lipid deficiency caused by FASN inhibition can be circumvented by increasing the uptake of exogenous lipids from the host, which would confer resistance to FASN inhibitors. In contrast to a very recent report in colorectal cancer, we demonstrate in OC cells (A2780, OVCAR3, SKOV3) that neither FASN inhibitors (G28UCM, Fasnall) nor FASN-specific siRNAs can stimulate a relief pathway leading to enhanced uptake of extrinsic FAs or low density lipoproteins (LDLs). Instead, we observed that the growth-arrest due to FASN inhibition or FASN knock-down was associated with significant dose- and time-dependent reduction in the uptake of fluorescently labelled FAs and LDLs. Western blotting showed that the expression of the FA receptor CD36, the LDL receptor(LDLR) and the lipid transport proteins fatty acid binding proteins 1–9 (FABP1–9) was not affected by the treatment. Next, we compared experimental blockade of endogenous lipid production with physiologic depletion of exogenous lipids. Lipid-free media, similar to FASN inhibitors, caused growth-arrest. Although lipid-depleted cells have diminished amounts of CD36, LDLR and FABPs, they can still activate a restorative pathway that causes enhanced import of fluorophore-labelled FAs and LDLs. Overall, our data show that OC cells are strictly lipid-depend and exquisitely sensitive to FASN inhibitors, providing a strong rationale for developing anti-FASN strategies for clinical use against OC.